Development of Secondary Layer of Wound Dressing Material Using Chitosan and Investigation for Hemostatic Efficiency. Issue 14 (28th October 2022) - Sivakumar, P.; Prakash, C.; Ramesh Babu, V.; Saravanan, D.
ABSTRACT: This study deals with effect of various concentrations of chitosan and material parameters on hemostatic properties of the woven and nonwoven dressings. The woven and nonwoven dressings are compared on efficacy on hemostasis. In addition to the studies on bio-polymer and minerals, 1% and 2% of chitosan particle dissolved solution were applied in both plain gauze and spunlace fabrics of cotton and viscose. The hemostatic efficacy and wound dressing suitability were analyzed and based on the results, the 2% chitosan viscose spunlace material was chosen due to its best performance for developing secondary layer for composite wound dressing.